A 42-year-old woman with acute myocardial infarction. Issue 19 (28th June 2018) - Fahey, James K; Ihdayhid, Abdul Rahman; White, Anthony John
Abstract : Clinical introduction: A 42-year-old woman presented with anterior ST elevation myocardial infarction. Urgent coronary angiography revealed tapering then occlusion of the distal left anterior descending (LAD) coronary artery with no flow in the distal LAD (figure 1A ). Balloon angioplasty with a 2.0×8 mm balloon re-established flow into the distal LAD. An angiogram of the right external iliac artery was also performed (figure 1B ). Question: Which of the following explains the abnormal appearance of the external iliac artery (figure 1B )? Atherosclerosis. Concertina effect. Fibromuscular dysplasia. Perforation. Multiple aneurysms.